Development of Interactive Learning Media in Occupational Health and Safety Subjectin Vocational High School - Retyana Wahrini; Chua Gim Peng (Universitas Negeri Yogyakarta, 2023)
Background: This research and development study aims to develop media in the form of learning videos on Occupational Safety and Health (K3) and to determine the feasibility of K3 learning videos in the Building Department of SMKN 5 Makassar.Methods: The development model used in this study is 4D (Four-D), namely the stages of defining, designing, developing, and disseminating. In this case, the learning video feasibility assessment data collection was carried out using a questionnaire as the research instrument. This study further involved 2 material experts and 2 media experts to assess the feasibility of the video. Students were also involved in getting responses to the Occupational Safety and Health (K3) learning video. Results: This study obtained interactive learning media through research and development methods with 4-D (Four-D) model development. Another result obtained is interactive learning media in the form of learning videos on occupational safety and health subjects in the Buildings Department of SMK N 5 Makassar. Furthermore, the results of the feasibility level of learning videos according to the material experts obtained a value of 89.13% which is categorized as very feasible. Meanwhile, the media experts gave a feasibility level of 89.84%, which is categorized as very feasible. In addition, the student responses as the users of learning video media gave value of 89.89%, which is categorized as very good.Conclusion: Based on this research, it is concluded that interactive learning media in the form of learning videos on Occupational Safety and Health subjects in the Building Department od SMK N 5 Makassar are suitable for use as a learning resource for students in the Building Department of SMK N 5 Makassar.